2022
DOI: 10.3389/fmicb.2022.961989
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with potassium-magnesium sulfate modulates the antioxidant capacity, immunity, and gut microbiota in weaned piglets

Abstract: The purpose of this study was to evaluate the effects of different levels of potassium magnesium sulfateon (PMS) on growth performance, diarrhea rate, intestinal morphology, antioxidant capacity, intestinal immunity, and gut microbiota in weaned piglets. A total of 216 weaned piglets were randomly divided into six dietary groups: the basal diet with 0% (CON), 0.15, 0.3, 0.45, 0.6, and 0.75% PMS. The results showed that the ADFI of 29–42 days and 1–42 days was linearly and quadratically increased by the PMS sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Romboutsia can regulate glucose metabolism through the production of short-chain fatty acids to stimulate insulin secretion, and it can also increase the carbohydrate content of feeds, which can have a lowering effect on blood glucose [ 45 ]. Peptostreptococcaceae is positively correlated with intestinal GSH-Px activity [ 46 ], and its reduced abundance is favorable to the body’s immunity [ 47 ]. The elevated abundance of Clostridium_sensu_stricto_1 leads to increased diarrhea in calves [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romboutsia can regulate glucose metabolism through the production of short-chain fatty acids to stimulate insulin secretion, and it can also increase the carbohydrate content of feeds, which can have a lowering effect on blood glucose [ 45 ]. Peptostreptococcaceae is positively correlated with intestinal GSH-Px activity [ 46 ], and its reduced abundance is favorable to the body’s immunity [ 47 ]. The elevated abundance of Clostridium_sensu_stricto_1 leads to increased diarrhea in calves [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that coated ZnO had a lower abundance of Clostridium_sensu_stricto_1 than CON and ZnO groups [ 6 ], which was controversial with our study. Peptostreptococcaceae was reported to have a positive correlation with intestinal GPx activity and to further improve antioxidant capacity in weaned piglets [ 47 ]. Shang et al [ 48 ] showed that probiotic Muribaculaceae presented a negative correlation with inflammation status in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al demonstrated that supplementation with MgSO 4 at doses of 200, 400, or 600 mg/kg resulted in a linear decrease in both the survival rate and litter weight at weaning, without affecting other parameters related to sow or litter performance. Moreover, dietary supplementation with potassium-magnesium sulfate could enhance growth performance, reduce diarrhea incidence, enhance antioxidant capacity, and modulate intestinal immunity in weaned piglets [ 19 ]. Andrea et al reported that the administration of an injected mineral supplement (Forssman) containing selenium, copper, potassium, and magnesium during summer months was found to effectively restore ovarian function in heat-stressed lactating dairy cows [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of K-containing compounds in drinking water reduced the heat stress of broilers [ 18 ]. In addition, it was reported that dietary supplementation with potassium-magnesium sulfate enhanced growth performance, reduced diarrhea incidence, and modulated the antioxidant capacity and intestinal immunity in weaned piglets [ 19 ]. However, the effects of the joint use of K and Mg on reproductive performance, antioxidant capacity, and immunity in sows in the gestation period remain unclear.…”
Section: Introductionmentioning
confidence: 99%